Kualitas Isi dan Kalimat Efektif pada Buku Antologi Cerpen Berjudul Dibalik Jendela Kamar Ibnu Abbas Terbitan Jejak Publisher sebagai Sumber Bacaan Siswa Kelas 8 SMP - Indah Zahri Rahmawati; Farizka Aziza Ramadhani; Muhammad Fahda Mahasin; Hanifah Ainurohmah; Widi Rahayu; Asep Purwo Yudi Utomo; Mochammad Usman Wafa (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
The use of effective sentences has a strong influence on the quality of the content of a work. In cerpen writing, it is necessary to use effective language so that both the written and the implied meanings of cerpen can be well conveyed. The study aims to describe the forms of error in the use of sentences effectively in the formation of content quality on cerpen, as well as to present a comprehensive analysis of the linguistic aspects in the cerpen anthology "Back the Window of Ibnu Abbas" as a source of reading for students of 8th grade high school. The study uses qualitative descriptive methods through a language analysis approach by evaluating the quality of the content and effectiveness of the sentences in the book. This research data is a sentence quotation in a cerpen in which there are written errors in the use of effective sentences. Data collection techniques are done with reading and recording techniques. The results of this study found: (1) repetition of verbs, (2) inappropriate dictionary selection, (3) passing sentences, and (4) ambiguous sentences in a cerpen. Such errors make sentences less effective and affect the quality of the cerpen content. The findings of this study provide an in-depth understanding of how the structure of sentences, the meaning of words, the context of language usage, and the form of words influence the understanding and experience of readers of a literary work.